Construction and characterization of a replicon system from a genotype II.4 isolate of norovirus - Jia, Huan (2014)
Norovirus (NoV) belong to genus Norovirus in virus family Caliciviridae. It is nowadays regarded as the major cause of human acute gastroenteritis all among the world within all age groups. There were still no anti-viral drugs or vaccines that can treat NoV due to lack of a stable in vitro cell culture system. This project focused on construction of a replicon system expressing green florescence protein (GFP) gene for Sydney 2012-like variant of NoV. The replication activity of this replicon would be tested in a few mammalian cell lines. Although the construction of replicon plasmid was not successful, the attempt to use PCR product of DNA replicon was successful in obtaining the replicon system. The positive GFP signals observed in A549 and H1299 cell lines after transfected with this DNA replicon suggested both cell lines were compatible for the replicon system. GFP-expressed DNA replicon as been described in this report might be used in further studies to test its replication activities in more cell lines while it could also be used as template to try cloning of replicon plasmid in future studies. Hopefully the established replicon system would be improved and might be used as a reference in anti-viral drugs and vaccines discovery.